The Illustrated encyclopedia of space technology - Gatland, Kenneth William, 1924- (New York : Orion Books, 1989)
Traces the history of man's conquest of space and assesses the potential for future satellite solar power stations, moon bases, and space colonies.
Includes bibliographical references and index.
Wilson's Senior High School.
Adult.
Adult
Keywords: Astronautics -- Dictionaries; Astronautics -- Dictionaries